Synthesis and Solution Region Optimization Method of a Straight-line Mechanism with Instant Center at Infinity - Qian Weixiang; Yang Yinshuo; Jin Zhichao; Qu Zhuocheng (Jixie chuandong)
A set of mechanism synthesis universal model is presented in this study. Given the expected straight-line and a fixed pivot, this model can solve the synthesis problem of the straight-line guide mechanism when the instant center tends to infinity in the coupler plane. In addition, mechanism synthesis formulas are derived and an example of mechanism optimization method is given. Based on the synthesis model, an infinite number of straight-line mechanism solutions that can satisfy the expected straight-line requirements are obtained. Then feasible solution regions are computed by imposing constraints. According to the design requirements, the designer can find promptly the optimal straight-line mechanism meeting constraints from an infinite number of mechanisms. The demonstration shows that this method provides a new way for straight-line mechanism synthesis with instant center at infinity, the synthesis process is simple and intuitive, and has universality. It is suitable for computer aided design of straight-line mechanism with second-order and third-order, which is beneficial to improve the design quality and compress the design cycle.